The food regimes of the indigenous amazon communities and their environmental impacts - Cartay, Rafael (2018)
The alimentary behavior of a group operates as a cultural strategy to ensure survival, recognizing itself within a culture that changes constantly, but that by inserting itself in the “tradition” maintains a cultural identity, which unites the group and differentiates it from others. The alimentary behavior or diet is the expression of structures of power, prestige of group and systems of subordination in the long term, in which substances that have a triple dimension as a nutrient, medicine and symbol are consumed. This article discusses the impacts caused to the environment by diets, and the positions of the critics of the Ecologically Noble Savage, arguing that indigenous Amazonian communities with little contact with urban society and the market produce moderate ecological damage, while they contribute to the expansion of the biodiversity of their environment in some aspects.